Trends in Evolution of Anthelminthic Chemical Agents: Ecological, Physiological and Biochemical Adaptation in Helminth - Dzhafarov, M. Kh.; Vasilevich, F. I. (Technological Innovation in Pharmaceutical Research Vol. 4, 2021)
The major anthelminthic substances - alternative medicine components, distinct types of pluripotent synthetic and naturally occurring chemicals – are discussed in this study. Much attention is paid to the sections devoted to recent discoveries (Emodepside, Monepantel, Derquantel, Tribendimidine) and to some promising works. The overview further covers certain elements of anthelminthic substance molecular mechanisms of action, helminth adaptability to anthelminthic chemicals, and alternate worming therapy alternatives. Anthelminthic substances are synthetic non-organic and organic or natural compounds. Based on the systemic analysis of particular features of the chemical structure of anthelminthic substances, the hypothesis on the viability of the targeted search for such compounds among the derivatives of conditionally progenitor cyclic hydrocarbons – benzene, indene, naphthalene, 1?-cyclopenth [a]-naphthalene and phenanthrene – by alternating absolutely unsaturated and saturated structures, including heterocyclic analogues containing nitrogen, oxygen and sulfur and different substitutes and functional groups, was voiced.